Gender Differences in Students’ Entrepreneurial Interest in Higher Education at Tangerang - Bambang Mardisentosa; Khusaini Khusaini (Bina Nusantara University, 2019)
This research aimed to analyze the differences in entrepreneurial interest between male and female students. The research used independent sample test approaches. The population was the students in Tangerang with a locus at Syekh-Yusuf Islamic University, Rahardja College of Information and Computer Management, and Yuppentek College of Technology with a total of 5.803 students. The samples consisted of 487 students using Slovin formulation that were taken randomly by using proportionate simple random sampling technique. The instrument used was the questionnaire. The model analysis was Mann-Whitney U-test and Kruskal-Wallis test. The result shows that the students’ entrepreneurial interest in Tangerang is included in the high category. The highest of students’ entrepreneurial interest is Rahardja College Information and Computer Management results prove that there is no difference in entrepreneurial interest between male and female students. It is because the students have gained the knowledge and comprehension of entrepreneurship. Significantly, the students’ entrepreneurial interests at Syekh-Yusuf Islamic University, Rahardja College of Information and Computer Management, and Yuppentek College of Technology are no different. This study contributes to the entrepreneurship and gender literature in the context of the economies of regions and developing countries.